Endovascular Stent Placement for Hemodialysis Arteriovenous Access Stenosis - Brendon L. Neuen; Richard A. Baer; Frank Grainer; Murty L. Mantha (International Journal of Vascular Medicine)
This study aims to report the outcomes of nitinol and polytetrafluoroethylene covered stent placement to treat hemodialysis arteriovenous access stenosis at a single center over a five-year period. Clinical and radiological information was reviewed retrospectively. Poststent primary and secondary patency rates were determined using Kaplan-Meier analysis. Ten clinical variables were subjected to multivariate Cox regression analysis to determine predictors of patency after stent placement. During the study period 60 stents were deployed in 45 patients, with a mean follow-up of 24.5 months. The clinical and anatomical success rate was 98.3% (59/60). Poststent primary patency rates at 6, 12, and 24 months were 64%, 46%, and 35%, respectively. Poststent secondary patency rates at 6, 12, and 24 months were 95%, 89%, and 85%, respectively. Stent placement for upper arm lesions and in access less than 12 months of age was associated with reduced primary patency (adjusted hazards ratio [HR] 5.1, p=0.0084, and HR 3.5, p=0.0029, resp.). Resistant or recurrent stenosis can be successfully treated by endovascular stent placement with durable long-term patency, although multiple procedures are often required. Stent placement for upper arm lesions and in arteriovenous access less than 12 months of age was associated with increased risk of patency loss.